2021
DOI: 10.1002/adfm.202104026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Efficient Singlet Oxygen Generators with Near‐Infrared AIE Features for Mitochondrial Targeted Photodynamic Therapy

Abstract: Aggregation‐caused fluorescence quenching with insufficient production of reactive oxygen species (ROS) has limited the application of photosensitizers (PSs) in fluorescence‐imaging‐guided photodynamic therapy (PDT). Aggregation‐induced emission PSs (AIE‐PSs) exhibit enhanced fluorescence intensity and a high efficiency of ROS generation in the aggregation state, which provides an opportunity to solve the above problems. Herein, a series of AIE‐PSs are successfully designed and synthesized by adjusting the D–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 63 publications
2
47
0
Order By: Relevance
“…42,43 With their superiority of negligible autofluorescence, low light scattering, deep detection depth, and less light damage to cells, AIE-active PSs with near-infrared (NIR) light are considered to be more favorable for imageguided PDT in comparison with visible light. [44][45][46] Therefore, AIE-active PSs with efficient ROS generation and longwavelength emission are highly and urgently required for effective treatment. 47,48 However, how to obtain a highly efficient and AIE-active PS with rapid and efficient ROS generation used for PDT remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 With their superiority of negligible autofluorescence, low light scattering, deep detection depth, and less light damage to cells, AIE-active PSs with near-infrared (NIR) light are considered to be more favorable for imageguided PDT in comparison with visible light. [44][45][46] Therefore, AIE-active PSs with efficient ROS generation and longwavelength emission are highly and urgently required for effective treatment. 47,48 However, how to obtain a highly efficient and AIE-active PS with rapid and efficient ROS generation used for PDT remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we and other authors reported some PSs with pyridinium or quinolinium blocks. 51–53 They can accumulate at cellular mitochondria and exhibit excellent mitochondrial targeting. At the same time, pyridinium and quinolinium derivatives also play an electron acceptor role in D–A conjugated molecules.…”
Section: Introductionmentioning
confidence: 99%
“…57,58 Finally, positively charged pyridinium and quinolinium derivatives were introduced into the receptor parts to target the mitochondria of cancer cells. 51 Accordingly, the main purpose of this work is to develop AIE-PSs with a strong D–A structure to achieve an excellent PDT effect.…”
Section: Introductionmentioning
confidence: 99%
“…Signicantly, such AIEactive dyes have exhibited great promise in the eld of biomedicine. [20][21][22][23] Luminogens characteristic of AIE (AIEgens) emit strong uorescence in the aggregated state with high photostability, which is ideal for cell-based and in vivo optical imaging. [24][25][26][27][28][29] In addition, appropriately designed AIEgens, exhibit superior photosensitization of molecular oxygen than common ACQ-based photosensitizers, 8,[30][31][32] thereby offering scope for the development of enhanced FI-guided PDT agents.…”
Section: Introductionmentioning
confidence: 99%